An Analysis of Gender Interpretation of the Phenomenon of Gamophobia - Noor M Rizki Kamils; Ardi Rizkiana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Gamophobia is a symptom that appears based on fear of marriage. There are several factors that make someone afraid to get married, including fear of losing their career and not wanting to be tied down by marriage. The aim of this research is to find out how the gamophobia phenomenon is viewed from a gender fair interpretation. This research uses qualitative research methods, descriptive analysis. As for collecting data using a library study approach. The results of this research are that talking about gamophobia, there are several reasons why someone chooses not to get married. Of the many problems that occur in cases of fear of marriage, there is fear of economic problems, past trauma, and bad experiences. However, if you look at the gender fair interpretation, there are several mufassir figures who choose not to marry because they want to dedicate their lives to worship and practicing knowledge.